Causal relationship between basal metabolic rate and kidney function: a bidirectional two-sample mendelian randomization study - Zhou, Chaomin; Peng, Yanzhe; Zhan, Lin; Zha, Yan (Frontiers in Endocrinology, 2024)
Background: The relationship between basal metabolic rate (BMR) and Chronic kidney disease (CKD) remains unclear and controversial. In this study, we investigated the causal role of BMR in renal injury, and inversely, whether altered renal function causes changes in BMR. Methods: In this two-sample mendelian randomization (MR) study, Genetic data were accessed from published genome-wide association studies (GWAS) for BMR ((n = 454,874) and indices of renal function, i.e. estimated glomerular filtration rate (eGFR) based on creatinine (n =1, 004, 040), CKD (n=480, 698), and blood urea nitrogen (BUN) (n =852, 678) in European. The inverse variance weighted (IVW) random-effects MR method serves as the main analysis, accompanied by several sensitivity MR analyses. We also performed a reverse MR to explore the causal effects of the above indices of renal function on the BMR. Results: We found that genetically predicted BMR was negatively related to eGFR, (β= −0.032, P = 4.95*10-12). Similar results were obtained using the MR-Egger (β= −0.040, P = 0.002), weighted median (β= −0.04, P= 5.35×10-11) and weighted mode method (β= −0.05, P=9.92×10-7). Higher BMR had a causal effect on an increased risk of CKD (OR =1.36, 95% CI = 1.11-1.66, P =0.003). In reverse MR, lower eGFR was related to higher BMR (β= −0.64, P = 2.32×10-6, IVW analysis). Bidirectional MR supports no causal association was observed between BMR and BUN. Sensitivity analyses confirmed these findings, indicating the robustness of the results. Conclusions: Genetically predicted high BMR is associated with impaired kidney function. Conversely, genetically predicted decreased eGFR is associated with higher BMR.